Effect of replacement of oats with dried sugar beet pulp on digestibility in horses - Emel Gürbüz; Behiç Coşkun (Eurasian Journal of Veterinary Sciences)
This research has been done in order to study the effects of molassed dried sugar beet pulp (MDSBP) supported by vegetable fat and soy bean meal instead of oat from the stand point of energy and protein on digestibility rate on horses. This research has been performed by using the 4x4 Latin Square method. The trail has been carried out in 108 days. Each period which is totally 27 days consists of 21 adaptation days and 6 digestion experiment days. In the trail, 4 different kinds of concentrated leed which is balanced within energy and protein were given to the control group, %12.5 MDSBP added group. %25 MDSBP added group and %37.5 MDSBP added group. In the amount of %1.2 of the live body weight. In the same way grass hay which is used as forage was also given in the amount off %1,2 of the live body weight. And by this way each horse was fed in the amount ol %2.4 of it's body weight. Although there are no differences according to diet in the live body weight and water consumption. No differences has been found in the digestion levels of the nutrient materials according to the diets in the digestion trails which were performed by classical and indicator method and performed in horses consuming four different diets. (P>0.05),